580 Vascular Distal Bypass Early Surveillance Audit. (12th October 2021) - Soliman, H; Halawa, M; Awad, R; Tan, J
Abstract: Introduction: Due to inconsistency in Duplex surveillance following distal bypass for peripheral arterial disease at our district general hospital. We planned an audit aiming to assess our current early surveillance of distal vascular bypass. Method: The latest twenty patients who underwent distal bypass were collected retrospectively from the theatre's records. Their clinical and imaging records were analysed to ascertain the timing of 1st duplex after the procedure. We also examined the discharge medications. We chose the standard advised by Society for Vascular Surgery that every patient following the procedure ideally should have (Clinical examination + ABPI + Duplex) at 1, 3, 6 and 12 months then annually. Results: 8 patients (40%) had a Duplex within 1 month, while 10% did not have a scan at all. Time range between the procedure and first Duplex was 1-11 months with a mean of 4 months. All patients were discharged on at least a single antiplatelet agent while only 70% were prescribed statins. Six patients needed an intervention for blocked graft but eventually failed, only one patient had a Duplex in a timely fashion, the stenosed graft was salvaged by angioplasty. Conclusions: There was no clear standardized surveillance protocol for vascular team juniors to follow. In addition, discharge of distal bypass patients sometimes is carried by general surgery team during weekends and unlikely that a Duplex is booked. We suggested booking the Duplex in theaters soon after performing the procedure to ensure inclusion in the surveillance protocol, education of junior doctors and re-auditing in 1 year.